Post radiation hysterectomy in locally advanced cervical cancer: Outcomes and dosimetric impact. Issue 3 (September 2016) - Mazeron, Renaud; Gouy, Sébastien; Chargari, Cyrus; Rivin del Campo, Eleonor; Dumas, Isabelle; Mervoyer, Augustin; Genestie, Catherine; Bentivegna, Enrica; Balleyguier, Corinne; Pautier, Patricia; Morice, Philippe; Haie-Meder, Christine
Abstract: Purposes: Firstly, to evaluate the impact of completion hysterectomy after chemoradiation and image-guided adaptive brachytherapy (IGABT) in locally advanced cervical cancer. Secondly, to assess a potential differential dose–effect relationship for the rectum and bladder according to the realization of hysterectomy. Material and methods: Two cohorts of patients were identified, differing by the realization of completion hysterectomy. Inclusions were limited to FIGO stage I–II, with no para-aortic involvement. All patients received a combination of pelvic chemoradiation followed by IGABT. Their outcomes and morbidity were reviewed. Log-rank tests were used to compare survivals. Probit analyses were performed to study dose–volume effect relationships. Results: The two cohorts comprised 54 patients in the completion surgery group and 157 patients in the definitive radiotherapy group. They were well balanced, except for the mean follow-up, significantly longer in the post hysterectomy cohort and the use of PET-CT in the work-up, more frequent in the definitive radiotherapy cohort. Although less local relapses were reported in the hysterectomy group, the 5-year disease-free and overall survival did not differ between groups. The cumulative incidence of severe late morbidity was significantly increased in the hysterectomy cohort: 22.5% versus 6.5% at 5 years ( p  = 0.016). Dose–volume effects were observed for the bladder, with the D2cm3 corresponding with a 10% probability of late severe morbidity urinary events (ED10 ) of 67.8 Gy and 91.9 Gy in the hysterectomy and definitive radiotherapy cohorts, respectively. A D90 CTVHR of 85 Gy (planning aim) corresponded with a 93.3% rate of local control in the definitive radiotherapy cohort whereas it corresponded with a 77.3% chance to have a good histologic response (complete response or microscopic residual disease) in the hysterectomy group. Conclusion: No benefit from completion hysterectomy in terms of overall or disease-free survival rates was observed, which was moreover responsible for an increase of the severe late morbidity. The realization of post-radiation hysterectomy resulted in a shift of the ED10 of 24.1 Gy.